IMPLEMENTASI METODE HAFALAN NADZOMAN KITAB ‘IMRITHI DALAM MEMAHAMI NAHWU SANTRI KELAS 2 TSANAWIYAH MADRASAH DINIYAH PUTRI PONDOK PESANTREN BABUSSALAM PAGELARAN MALANG - Muhammad Arif Nasruddin, Nafisatus Saidah (JIPI (Jurnal Ilmiah Pendidikan Islam), 2026)
This study is motivated by the low level of understanding among second-grade Tsanawiyah students at the Madrasah Diniyah Putri of Babussalam Islamic Boarding School. In essence, each student demonstrates varying levels of comprehension according to their individual abilities. Some students are able to grasp and understand the material immediately, while others require several stages or processes to fully comprehend the explanations delivered by their teachers. The research problem addressed in this study is: how is the implementation of the memorization method of nadzoman from the Imrithi book in enhancing students’ understanding of nahwu among second-grade Tsanawiyah students at the Madrasah Diniyah Putri of Babussalam Islamic Boarding School, Pagelaran Malang? Accordingly, the objective of this study is to examine the implementation of the memorization method of nadzoman from the Imrithi book in improving students’ understanding of nahwu. This research employs a descriptive qualitative method based on Sugiyono’s theoretical framework. Data were collected through observation, interviews, and documentation. The findings of this study indicate that the implementation of the memorization method of nadzoman from the Imrithi book significantly improves students’ understanding of nahwu material in an easier and more efficient manner. Students demonstrate progress in memorizing each verse of the nadzoman fluently. In addition, students are able to comprehend the nahwu material presented in the Imrithi book and successfully memorize the corresponding verses for each topic. Keywords: Memorization Method, Nahwu, Material Comprehension, Nadzoman.